2016
DOI: 10.1016/j.eurpsy.2016.01.981
|View full text |Cite
|
Sign up to set email alerts
|

LGBT adolescents in America: Depression, discrimination and suicide

Abstract: IntroductionThe mental health of Adolescents in America is a major concern for the field of psychiatry. In particular, Lesbian, Gay, Bisexual and Transgender (LGBT) adolescents are at higher risk of adverse mental health outcomes. This is largely attributed to “minority stress” and from outright bullying and discrimination. In this presentation, this link between bullying and depression will be explored.ObjectivesBy the end of this presentation, the audience will be able to better understand the link between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…non-US born, LGBT, obese/underweight). We found that racial/ethnic discrimination imposes a unique psychological stress that is significantly associated with childhood suicidality with a magnitude of effect similar to well established risk factors like sexual orientation-based discrimination 31 and weight-based discrimination. 32 Notably, the data analyzed in the current study was collected in 2018, two years before the COVID-19 pandemic, post-election furor, and the prominent racial justice protests of 2020-2021; therefore, our findings may have been even more pronounced had the data been collected today, in 2021.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…non-US born, LGBT, obese/underweight). We found that racial/ethnic discrimination imposes a unique psychological stress that is significantly associated with childhood suicidality with a magnitude of effect similar to well established risk factors like sexual orientation-based discrimination 31 and weight-based discrimination. 32 Notably, the data analyzed in the current study was collected in 2018, two years before the COVID-19 pandemic, post-election furor, and the prominent racial justice protests of 2020-2021; therefore, our findings may have been even more pronounced had the data been collected today, in 2021.…”
Section: Discussionsupporting
confidence: 55%
“…We demonstrate that experiences of racial/ethnic discrimination are significant stressors whose magnitude of association with increased suicidality is similar to that of well-established risk factors, such as sexual orientation-based discrimination 31 or history of depression. 45 Therefore, clinicians should be mindful of this unique stressor and consider this as a potential contributor to suicide risk.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…According to literature reviews, depression was found to be prevalent in the sexual minority, which risk of depression was 2.6 times higher among gay men (Wang et al., 2014). Furthermore, research has shown that compared to heterosexuals, LGBT adolescents in America have 4–5 times greater odds of suicidal attempts stemming from bullying and discrimination in schools (Ahuja, 2016).…”
Section: Introductionmentioning
confidence: 99%